Akulturasi Islam dalam Adat Pengesahan Perkawinan Suku Sakai Solapan Kabupaten Bengkalis, Riau - Ellya Roza; Yasnel Yasnel; Mirawati Mirawati (TSAQAFAH, 2019)
AbstractThis paper aims to reveal the acculturation of Islam with the customary endorsement of the marriage of the Sakai tribe community in the Bathin Solapan region in Bengkalis Regency, Riau. As a native tribe, Sakai has a strong belief in his culture, especially marriage by using various social symbols with Bathin as the main character who becomes the legitimate determinant of a marriage. Likewise the shrill of a dog in Bathin's house is a benchmark for the validity of a marriage. Because this study is a study of social and cultural heritage that integrates with Islam, the methodology used in accordance with the concept of social science research is a qualitative descriptive method that focuses on content analysis with several stages of work through the concept of Research and Development (R & D) . At the end of the study it was found that the social symbol in the custom of the marriage of the Sakai tribe in the Bathin Solapan region was (1) Bathin who started with a picture of a puppet at the pole of his house using betel lime. After that the bride's second hand is put together with the position of the man's hand on the woman's hand. Then a family testimony was held for both parties: (2) The dog's curse which was beaten by Bathin as the validity of a marriage. With the Islamization in Riau, there was an acculturation of Islam towards the customary ratification of the Sakai tribe marriage which was implemented using Islamic social symbols which were manifested in the pillars of marriage and full of marriage with the nikah as the main actor.Keywords: Acculturation of Islam, Social Symbols, Ratification of Marriage, Sakai Tribe, BatinAbstrakTulisan ini bertujuan mengungkap akulturasi Islam dengan adat pengesahan perkawinan  masyarakat suku Sakai dalam wilayah Bathin Solapan di Kabupaten Bengkalis, Riau. Sebagai suku asli, Sakai memiliki keyakinanan yang kokoh terhadap kebudayaannya terutama perkawinan dengan menggunakan berbagai symbol social dengan Bathin sebagai tokoh utamanya yang menjadi penentu sah atau tidaknya sebuah perkawinan. Demikian juga lengkingan seekor anjing yang ada di rumah Bathin menjadi tolok ukur terhadap sahnya sebuah perkawinan. Dikarenakan penelitian ini merupakan kajian terhadap peninggalan social dan budaya yang berintegrasi dengan Islam, maka metodologi yang digunakan sesuai dengan konsep penelitian ilmu-ilmu social yakni metode deskriptif kualitatif yang menfokuskan kepada content analysis dengan beberapa tahapan kerja melalui konsep Research and Development (R & D). Pada akhir kajian ditemukan bahwa symbol social dalam adat pengesahan perkawinan suku Sakai  di wilayah Bathin Solapan  adalah (1) Bathin yang memulai dengan gambar orang-orangan di tiang rumahnya dengan menggunakan kapur sirih. Setelah itu tangan kedua calon pengantin disatukan dengan posisi tangan laki-laki di atas tangan perempuan. Kemudian diadakan kesaksian keluarga bagi kedua belah pihak: (2) Lengkingan anjing yang dipukul oleh Bathin sebagai sahnya sebuah perkawinan. Dengan adanya Islamisasi di Riau, maka terjadi akulturasi Islam terhadap adat pengesahan perkawinan suku Sakai yang diimplementasikan dengan menggunakan symbol sosial agama Islam yang wujud pada rukun nikah dan sarat nikah dengan pengulu nikah sebagai actor utamanya.Kata Kunci:  akulturasi Islam, symbol sosial, pengesahan perkawinan, Suku Sakai